STRUCTURE AND THERMAL STABILITY OF THE BENZO-15-CROWN-5 WITH LANTHANUM (III) BROMIDE COMPLEX - Muhammad Idiris Saleh; Eny Kusrini; Abdulssalam Salhin; Rohana Adnan; Ismail Ab. Rahman; Bahruddin Saad; Bohari M. Yamin (Indonesian Journal of Chemistry, 2004)
The reaction of benzo-15-crown-5 (C14H20O5) ligand with La(NO3)3.7H2O in the presence of HBr has resulted in the production of an exotic sandwich complex, [LaC28H36Br4O10][3Br]. The crystal system is triclinic with space group P1, a = 12.5834(14) Å, b = 13.5816(16) Å, c = 13.8403(16) Å, a = 70.751(2)°, b = 66.773(2)° and g = 67.631(2)°. The cation comprises of the lanthanum atom coordinated to two crowns via three oxygen atoms from each crown in a η3-sandwich fashion. The two phenyl groups of the crown are brominated. The La-OLigand bond lengths are between 2.857(7) and 2.949(7) Å. The trianion [3Br]3- is linear with Br-Br bond lengths of 2.518(2) and 2.560(2) Å respectively. The molecule is stabilized by intermolecular interactions of the type C-H...Br to form dimers and are arranged parallel to bc face.